Continuous separation and manipulation of particles and cells using dielectrophoresis - Lewpiriyawong Nuttawut (2011)
Cell manipulation and separation are critical in biomedical diagnosis. Typical techniques such as flow cytometry require costly and bulky instruments. Microfluidics holds promise in minimization and integration of such biomedical routine processes onto a portable and affordable chip. It also offers faster analysis with less sample/reagent volume. Field-Flow Fractionation (FFF) employing dielectrophoresis (DEP) in microfluidics is an emerging technique for continuous manipulation and separation of cells. Although microfluidic DEP-FFF techniques can overcome some FFF-associated problems such as sample band broadening and slow separation, most microfluidic DEP-FFF devices utilize AC electric field generated by metal electrodes fabricated on silicon or glass substrates. This study focuses on implementation of DEP-FFF techniques into polymer microfluidic devices for continuous separation, sorting, and concentration of particles and cells. The modified PDMS-based H-filter platform with multi-insulating blocks is developed for sorting and continuous separation of particles. The use of a single-channel DC power supply greatly simplifies the device operation. The multi-insulating blocks not only can enhance DC-DEP force but also focus particles in a small region, thereby facilitating particle separation. In order to establish critical guidelines for optimal device configurations, the effects of the number and geometrical structures of insulating blocks on the threshold voltages are investigated. The effectiveness of the proposed technique using combined AC and DC field is experimentally and numerically evident by reducing the threshold voltage in separation. Moreover, a novel microfluidic technique utilizing a combined AC and DC electric field is also developed for particle and cell concentration under a continuous-flow condition. Findings obtained from both the experiments and simulation show a significant reduction in the threshold voltage by 85.9%. Experimental results suggest that higher buffer concentration, larger particle size and higher ratio of AC-to-DC electric fields improve DEP concentration performance. In addition, a new PDMS-based microfluidic device with 3D conducting PDMS composites as sidewall electrodes is developed for characterization and separation of particles and cells by AC-DEP. The developed fabrication technique greatly facilitates (i) the integration of the conducting PDMS composite electrodes with PDMS microchannels, and (ii) device assembly by using only oxygen plasma treatment. With these features, the device can be operated at relatively high flow rates without liquid leakage. Unlike conventional 2D planar electrodes, 3D conducting PDMS electrodes can produce 3D electric field that distributes uniformly throughout the entire channel height and varies along the channel lateral direction, thereby giving rise to stronger DEP forces and also allowing for lateral manipulation and observation of particles and cells. The high efficiency (>97%) proves the device capability to effectively separate various samples including submicron particles, micron particles, live and dead yeast cells and bacterial cells under continuous-flow conditions.